2022
DOI: 10.1001/jamanetworkopen.2022.38961
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Humoral Immunodeficiency With Bispecific Antibody Therapy in Relapsed Refractory Multiple Myeloma

Abstract: This case series describes the kinetics of humoral deficiency in patients with relapsed refractory multiple myeloma treated with bispecific antibodies, the infectious complications, and response to COVID-19 immunization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 6 publications
0
38
0
Order By: Relevance
“…A trial of T cell/FCRH5 BsAb reported grade ≥3 infection of 19% and limited data is available for NK targeting BsAb [3,9]. Real world data on rates of hypogammaglobulinaemia, impact of immunoglobulin replacement, and associated rates of infection are starting to emerge, however more evidence is necessary [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…A trial of T cell/FCRH5 BsAb reported grade ≥3 infection of 19% and limited data is available for NK targeting BsAb [3,9]. Real world data on rates of hypogammaglobulinaemia, impact of immunoglobulin replacement, and associated rates of infection are starting to emerge, however more evidence is necessary [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the lack of universal uptake of COVID-19 vaccination, suboptimal vaccines response has been demonstrated in recipients of CAR T-cell and BsAb therapy. 26,52 Additionally, COVID-19 remains a significant concern to patients with MM with mortality as high as 14% in recipients of BCMA directed T-cell therapy. [53][54][55] Given the high rate of US COVID19 infection, and reasonable uptake of vaccination in some geographical areas, high titers of COVID19 neutralizing antibodies are now reported in IVIG products.…”
Section: Viral Infectionsmentioning
confidence: 99%
“…Additionally, BCMA is essential for survival of long‐lived plasma cells, further explaining profound plasma cell aplasia seen with BCMA‐targeted therapies 25 . Notably, both BsAb and CAR T‐cell therapy led to profound and prolonged hypogammaglobulinemia 26,27 . In the pivotal KarMMa trial (idecabtagene vicleucel/ide‐cell, CAR T‐cell), any‐grade hypogammaglobulinemia was reported in 5% of patients at ≤8 weeks, 16% of patients at >8 weeks and ≤6 months, and 2% of patients at >6 months 6 .…”
Section: Mechanisms Of Immunosuppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, chimeric antigen receptor (CAR) T-cells and bispecific T-cell engagers (BiTEs) targeting B-cell maturation antigen (BCMA) have resulted in unprecedented response rates 1 . While infections remain the leading cause of morbidity and mortality in patients with relapsed/refractory multiple myeloma (RRMM) 2 , the on-target-off-tumor toxicities associated with BCMA-targeting agents lead to prolonged B-cell aplasia, hypogammaglobulinemia, and increase the cumulative risk for infections [3][4][5][6] .…”
mentioning
confidence: 99%